2019
DOI: 10.15252/embr.201847468
|View full text |Cite
|
Sign up to set email alerts
|

Myogenin promoter‐associated lnc RNA Myoparr is essential for myogenic differentiation

Abstract: Promoter‐associated long non‐coding RNAs (lncRNAs) regulate the expression of adjacent genes; however, precise roles of these lncRNAs in skeletal muscle remain largely unknown. Here, we characterize a promoter‐associated lncRNA, Myoparr, in myogenic differentiation and muscle disorders. Myoparr is expressed from the promoter region of the mouse and human myogenin gene, one of the key myogenic transcription factors. We show that Myoparr is essential both for the specification of myoblasts by activating neighbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 62 publications
(93 reference statements)
8
67
0
Order By: Relevance
“…They found that, in denervated muscles, Myoparr knockdown prevents atrophy by activating the bone morphogenetic protein signaling and by increasing the expression of GDF5, a muscle atrophy inhibitor. The existence of a Myoparr human counterpart makes the lncRNA potentially eligible as therapeutic target for neurogenic atrophy (Hitachi et al, 2019b).…”
Section: Nuclear-enriched Lncrnasmentioning
confidence: 99%
“…They found that, in denervated muscles, Myoparr knockdown prevents atrophy by activating the bone morphogenetic protein signaling and by increasing the expression of GDF5, a muscle atrophy inhibitor. The existence of a Myoparr human counterpart makes the lncRNA potentially eligible as therapeutic target for neurogenic atrophy (Hitachi et al, 2019b).…”
Section: Nuclear-enriched Lncrnasmentioning
confidence: 99%
“…We previously identified an lncRNA, Myoparr, from the promoter region of the myogenin gene, which codes for a transcriptional factor that is indispensable for skeletal muscle differentiation [34]. Myoparr interacts with a transcriptional co-activator, DEAD (Asp-Glu-Ala-Asp) box polypeptide 17 (Ddx17), and is essential both for the specification of myoblasts into the differentiation lineage and for the myoblast cell cycle withdrawal.…”
Section: Introductionmentioning
confidence: 99%
“…But since the exogenous pncRNA-D suppressed the proliferation of HeLa cells, there is a possibility that it could also work in trans. Several lncRNAs have been reported to work both in cis and in trans (57,58), but generally, individual lncRNA regulate different genes in cis or in trans. However, there is lncRNA such as ANRIL, which is able to reduce expression of neighboring gene (CDKN2B) both in cis and in trans (59).…”
Section: Discussionmentioning
confidence: 99%